2021
DOI: 10.1002/aur.2661
|View full text |Cite
|
Sign up to set email alerts
|

Toward a cumulative science of vocal markers of autism: A cross‐linguistic meta‐analysis‐based investigation of acoustic markers in American and Danish autistic children

Abstract: Acoustic atypicalities in speech production are argued to be potential markers of clinical features in autism spectrum disorder (ASD). A recent meta-analysis highlighted shortcomings in the field, in particular small sample sizes and study heterogeneity. We showcase a cumulative (i.e., explicitly building on previous studies both conceptually and statistically) yet self-correcting (i.e., critically assessing the impact of cumulative statistical techniques) approach to prosody in ASD to overcome these issues. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 57 publications
(75 reference statements)
5
39
3
Order By: Relevance
“…The dataset used in this study consists of voice recordings collected in previous studies for other purposes and their content has been analyzed in other published research (Cantio et al, 2016; Fusaroli et al, 2022; Grossman et al, 2013). For demographic, clinical and cognitive information about the participants, see Table 1 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dataset used in this study consists of voice recordings collected in previous studies for other purposes and their content has been analyzed in other published research (Cantio et al, 2016; Fusaroli et al, 2022; Grossman et al, 2013). For demographic, clinical and cognitive information about the participants, see Table 1 1 .…”
Section: Methodsmentioning
confidence: 99%
“…The US English dataset included 50 autistic (187 recordings, 149 minutes) and 31 NT (122 recordings, 56 minutes) participants, retelling stories (Grossman et al, 2013). The recordings had been collected and analyzed for different purposes in previous studies (Cantio et al, 2016; Fusaroli et al, 2022; Grossman et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…The most useful outcome for training new clinicians, for example, would be to identify a set of easily-identified acoustic features that have been shown to be characteristic of the speech of autistic people. Neither a long list of relatively complex acoustic features nor an inscrutable composite component from PCA achieves this goal (see supporting information S4 of Fusaroli et al (2021) for a discussion of the interpretation of PCA components in acoustic analysis). While likely incomplete, a list of approximately three to five intuitively understandable features may be of the greatest utility for intervention.…”
Section: Q4 How Do These Clusters Relate To Subjective Ratings By Naï...mentioning
confidence: 99%
“…A recent systematic review and meta-analysis (Fusaroli, Lambrechts, Bang, Bowler, & Gaigg, 2017) highlights several potential acoustic contributors to group differences. The meta-analytic findings point to higher pitch, and increased pitch variability, number of pauses and pause duration, although replication attempts show these patterns might be not be generalizable across languages and samples (see, Fusaroli et al 2021). While some studies have found that acoustic differences map onto expert clinician ratings of autism-specific symptoms (McCann et al, 2007; Study 1, Diehl et al 2009), these findings have not always replicated, even within the same lab (Study 2, ibid;Fusaroli et al 2021).…”
mentioning
confidence: 99%
“…To move beyond this situation, this study showcases a cumulative scientific approach capable of systematically assessing the impact of previous findings on current data and integrating the new findings into a global framework. Such a framework promotes the systematic assessment of previous findings and different automated measures of coherence across contexts and samples with different clinical, demographic, cultural and linguistic profiles (Corcoran et al, 2018; Fusaroli et al, 2021; Rybner et al, 2021). This will provide a more robust predictive performance assessment, but it may also provide more reliable foundations for theory development (e.g.…”
Section: Introductionmentioning
confidence: 99%